Migrants, Identity and Radical Politics: Meaning and Ramifications of the Visits of Italian Communist Party Officials to Australia. (June 2017) - Battiston, Simone
Abstract : This paper examines ten years (1963–1973) of visits to Australia of Italian Communist Party (PCI) officials. In particular, the visits' origins, meaning and ramifications are analysed and framed against the background of post‐war migrant worker identity discourses and radical politics. They appear to have shaped markedly the direction of the experience of Italian communists in Australia, especially in Sydney, and their interaction with both the Communist Party of Australia (CPA) and the PCI. Ultimately, they helped spread the message of Italian communism among migrants and encourage the replication on Australian soil of the successful experience of the Europe‐based PCI federations with thousands of worker members. For the CPA, which had been looking for new ways to break through to the hearts and minds of the migrant proletariat, the visits heralded a stronger partnership with its Italian members, a closer link with Eurocommunism, and a potential new stream of recruits that would have reversed the hemorrhaging of membership. The visits were instrumental, as argued in this paper, for the establishment and promotion of an Italian cultural and language space for which far‐left Italian migrants in Australia had long yearned.